A comparison between eurocode 3 (1992) and British standard 5950 (2000) for flexural member design - Franky, Ajie (University Malaysia Sarawak (UNIMAS), 2006)
The European Standards and British Standards are the standards used in design of structural steel. This project is about the comparisons between the two standards with respect to a flexural member design. There are few methods of comparison used int his project. These methods include notation, load factors, load combinations and design considerations, an example of flexural member design, the safety factors, economical factors, advantages and disadvantages of these two standards.